P95 "Why do we have to lose this too?": an exploration into the conversations around intimacy that individuals with Sjögren's syndrome have on an online forum. (20th April 2020) - McCready, Jemma L; McCarty, Kristofor; Deary, Vincent; Collins, Tracy L; Hackett, Katie L
Abstract: Background: Sjögren's syndrome (SS) is an autoimmune disease that predominantly affects women (by a ratio of 9:1), and age at onset is typically between 40-60 years. Symptoms of dryness of the vagina and vulva can cause painful sexual intercourse and can result in diminished levels of sexual arousal and desire. This can lead to a lack of understanding by their partner, which can place an immense strain on their relationship. Furthermore, intimacy issues can be a particularly sensitive subject and often go undiscussed, even between partners, which can leave them feeling isolated and without an adequate support network. Many patient groups turn to online support forums and use these sites to discuss sensitive issues under the cloak of anonymity. Analysing this source of data allows us to explore the conversations pertaining to intimacy issues that individuals with SS may not feel comfortable discussing in person. Methods: The forum data was scraped using the automated Web Scraper tool, accessed from the developer tools within Google Chrome. The Computer-Assisted Qualitative Data Analysis (CAQDAS) software tool ATLAS.ti was used to facilitate the data analysis process. The process of analysis was conducted in accordance with both Braun and Clarke's Thematic Analysis (TA) framework and Freise, Sorrato and Pires guidelines for applying the phases of TA within the ATLAS.ti software. Results: A total of 3, 557 posts were identified as being pertinent to the topic of intimacy. Conversations were centred around the lack of sexual activity with their partners, with users revealing they had been abstaining for years as a result of vaginal dryness, dyspareunia, fatigue and widespread pain. Numerous users discussed being unable to engage in intimate activities like handholding and hugging due to allodynia and issues with temperature regulation, as well as refraining from kissing as they perceived others kisses to be too wet and sloppy. One conversation theme was centred around increased cognitive effort and behaviour changes, with many users revealing that they plan sexual activity around symptoms, regularly implement self-management strategies before, during, and after sexual activity, and use smaller gestures to show emotion. There was also a body of conversation focused around the emotional impacts of sexual dysfunction with users unanimously discussing their experience with feelings of guilt, burden, fear of intimacy and pain, and saudade - a deep emotional state of longing for the past and their previous selves. Conclusion: Individuals with SS experience alterations in their sexual activity and relationship dynamics, with symptoms of vaginal dryness, fatigue and pain being discussed as the most debilitating of symptoms. Disclosures: J.L. McCready None. K. McCarty None. V. Deary None. T.L. Collins None. K.L. Hackett None.